Exchange Rate Shocks and Domestic Price Adjustment in Southeast Asia - Nur Amirah binti Ismail; Aiman Hakimi; Daniel Lim Wei Jun; Katrina Mae Villanueva; Paolo Gabriel Mendoza (Journal of Economics Business Industry, 2026)
Exchange rate pass-through (ERPT) has emerged as a central concern for monetary authorities in open emerging economies navigating the dual pressures of external volatility and domestic price stability. This study examines the dynamics of ERPT in three Southeast Asian economies  Malaysia, Thailand, and the Philippines over the period from 2010 to 2024. The analysis employs a Vector Autoregressive (VAR) model and a Vector Error Correction Model (VECM), with Cholesky decomposition for structural identification. Impulse response functions (IRFs) trace the response of producer prices, import values, and consumer prices to real effective exchange rate shocks over a twelve-month horizon. The Johansen cointegration procedure confirms long-run equilibrium relationships among variables, and the Granger causality test is applied to determine the direction of short-run causality. The findings indicate that ERPT to consumer prices is low and incomplete across all three countries, though heterogeneous in magnitude and persistence. Malaysia exhibits a unidirectional causal flow from the real effective exchange rate (REER) to the Consumer Price Index (CPI), with a low long-run pass-through coefficient of 0.145. Thailand shows an insignificant short-run response to REER shocks, consistent with its credible inflation-targeting framework, yet a moderate long-run estimate of 1.089. The Philippines records the highest pass-through coefficient of 1.823 in the long run, reflecting its greater exposure to external price pressures and more volatile currency dynamics. The error correction terms are negative and significant in all three countries, confirming a self-correcting mechanism toward long-run price equilibrium. These findings carry important implications for the design of inflation-targeting frameworks, the management of exchange rate regimes, and subsidy reform strategies across ASEAN economies.